PENGEMBANGAN MEDIA PEMBELAJARAN ARTIFICIAL INTELLIGENCE (AI) BERBASIS MODEL PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Pratiwi, Riesha; Desyandri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the suboptimal quality of lesson planning and implementation in Pancasila Education at the elementary school level. The learning models applied by teachers have not been maximized, and the instructional media used remain limited, particularly in presenting concrete visualizations such as contextual illustrations. As a result, students with lower abilities tend to be passive during discussions due to limited understanding of the learning context. Therefore, this study aimed to develop an Artificial Intelligence (AI) based instructional media integrated with the Problem Based Learning (PBL) model in Pancasila Education that is valid, practical, and effective. This research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The developed AI-based learning media was validated by material, media, and language experts before being tested for practicality and effectiveness. Practicality was measured through teacher and student response questionnaires, while effectiveness was assessed using pretest and posttest scores. The research was conducted at SD Islam Al-Ishlah Bukittinggi (trial school), MIS Al-Ikhwan and SDI Cendekia (implementation schools), and SD Jamiyyatul Hujjaj (control class). The results showed that the AI-based learning media achieved an overall validity score of 97.33% (very valid). Practicality results indicated 100% (teacher) and 91.20% (students) in the trial phase with an N-Gain score of 84.5 (high). In the implementation phase, practicality reached 86% (teacher) and 86.1% (students) with an average N-Gain of 81.16 (high) at MIS Al-Ikhwan, and 100% (teacher) and 90% (students) with an average N-Gain of 94.78 (high) at SDI Cendekia. Meanwhile, the control class obtained an average score of 47.53 (moderate). Thus, the AI-based PBL instructional media is proven to be valid, practical, and effective for use in Pancasila Education learning at the elementary school level.